Ultimate bearing capacity of composite beams with reinforced web opening under hogging moment: Practical calculation method. (January 2023) - Zhou, Xiang; Liao, Wenyuan; Liu, Dewen
Abstract: An experiment was conducted using an empty belly truss as the mechanical model. Based on the results, the secondary bending moment function was derived according to the plastic stress distribution on the four corner sections of the opening mouth under the limit state. An ultimate bearing capacity calculation method of the web opening composite beam in the hogging bending moment region with reinforcement measures was established. This method considers the shear capacity of the concrete slab above the opening, which more closely approximates actual engineering practice. The results indicated that the shear capacity of the openings in the web hogging bending moment region can be effectively improved by installing stiffeners at the openings. Moreover, the bearing capacity increased with an increase in the area of the reinforcing plate, and the concrete slab significantly contributed to the shear bearing capacity. The theoretical results aligned with the experimental results obtained using the finite part method, and the accuracy and reliability of the proposed method were verified.